2007
DOI: 10.1042/bj20070449
|View full text |Cite
|
Sign up to set email alerts
|

DGA1 (diacylglycerol acyltransferase gene) overexpression and leucine biosynthesis significantly increase lipid accumulation in the Δsnf2 disruptant of Saccharomyces cerevisiae

Abstract: We previously found that SNF2, a gene encoding a transcription factor forming part of the SWI/SNF (switching/sucrose non-fermenting) chromatin-remodelling complex, is involved in lipid accumulation, because the Deltasnf2 disruptant of Saccharomyces cerevisiae has a higher lipid content. The present study was conducted to identify other factors that might further increase lipid accumulation in the Deltasnf2 disruptant. First, expression of LEU2 (a gene encoding beta-isopropylmalate dehydrogenase), which was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 44 publications
(57 reference statements)
9
56
0
Order By: Relevance
“…In addition to that, our preliminary bioreactor fermentation using YNB-Ura, without additional leucine supplementation, resulted in less biomass and LCDCA production from the M strain (Biomass up to 7 g/L and maximum LCDCA of 3 g/L). Similalrly, addition of leucine was reported to increase the growth and lipid accumulation in S. cerevisiae devoid of active SNF2 [105].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, our preliminary bioreactor fermentation using YNB-Ura, without additional leucine supplementation, resulted in less biomass and LCDCA production from the M strain (Biomass up to 7 g/L and maximum LCDCA of 3 g/L). Similalrly, addition of leucine was reported to increase the growth and lipid accumulation in S. cerevisiae devoid of active SNF2 [105].…”
Section: Discussionmentioning
confidence: 99%
“…Total lipid production from glycerol was less than 12% dcw but represented nearly a doubling over empty vector control (Yu et al, 2013), and up to 17% dcw lipids, a four-fold increase by over-expression of FAS1, FAS2, and ACC1 with small amounts (up to 4 g/L) of ethanol being produced (Runguphan and Keasling, 2014). Previous work has shown that a SNF2 delete strain with over-expression of DGA1 or a DGA1 variant lacking the N-terminal 29 amino acids could accumulate lipids up to 45% and 50% dcw on 5% and 10% glucose, respectively (Kamisaka et al, 2007;Kamisaka et al, 2013). The gene SNF2 codes for an ATPase subunit of the SWI-SNF chromatin remodeling complex (Peterson and Tamkun, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Animals with reduced DGAT activity are resistant to diet-induced obesity Smith et al, 2000) and lack milk production (Smith et al, 2000). Over-expression of DGAT enzymes increases TAG content in plants (Andrianov et al, 2010;Bouvier-Nave et al, 2000;Burgal et al, 2008;Durrett et al, 2010;Jako et al, 2001;Lardizabal et al, 2008;Xu et al, 2008), animals (Kamisaka et al, 2010;Liu et al, 2009;Liu et al, 2007;Roorda et al, 2005), and yeast (Kamisaka et al, 2007). DGATs have nonredundant functions in TAG biosynthesis in species such as mice (Stone et al, 2004) and tung tree (Vernicia fordii) (Shockey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%